Environment Impacts and Composition - Biotoxic Activity in Natural Hydrocarbon Raw Materials & Processed Products - Trinh Quoc Vinh; Dinh Tran Ngoc Huy; Sergey Yakutseny (Journal La Lifesci, 2022)
The paper aims to figure out What are environment impacts and composition - biotoxic activity in natural hydrocarbon raw materials and processed products. By using descriptive method for primary model, synthesis methods and process analysis and analysis of difficulties and discussion, The study of this problem point that, to assess the environmental impact of hydrocarbons on the biosphere, an accurate knowledge of the physical properties and chemical composition of oil and gas. Numerous tragic examples of accidents, such as those associated with a leak hydrogen sulfide gases. Hydrogen sulfide, due to its higher density relative to air settles in the lowlands of the relief, accumulating in calm weather in concentrations up to lethal. This leads to the death of animals and the death of people. The latter could be avoid by going to elevated windward areas, i.e., knowing the physical properties of this toxic gas.